2022
DOI: 10.1103/physrevlett.128.075901
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Control of Soft Chiral Phonons in PbTe

Abstract: PbTe crystals have a soft transverse optical phonon mode in the terahertz frequency range, which is known to efficiently decay into heat-carrying acoustic phonons, resulting in anomalously low thermal conductivity. Here, we studied this phonon via polarization-dependent terahertz spectroscopy. We observed softening of this mode with decreasing temperature, indicative of incipient ferroelectricity, which we explain through a model including strong anharmonicity with a quartic displacement term. In magnetic fiel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Recent theoretical reports (22)(23)(24) have proposed that a phonon magnetic moment can arise from the time-dependent electric polarization induced by a laser-driven infrared-active phonon. However, the predicted magnitude of the phonon magnetic moment, which depends on the phonon effective charge and the ion masses, is relatively small compared to recent experimental observations (19,21). Larger values compatible with experiments can be obtained when electronic contributions are considered (25)(26)(27).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…Recent theoretical reports (22)(23)(24) have proposed that a phonon magnetic moment can arise from the time-dependent electric polarization induced by a laser-driven infrared-active phonon. However, the predicted magnitude of the phonon magnetic moment, which depends on the phonon effective charge and the ion masses, is relatively small compared to recent experimental observations (19,21). Larger values compatible with experiments can be obtained when electronic contributions are considered (25)(26)(27).…”
Section: Introductionmentioning
confidence: 65%
“…3 (D to F). The magnetic properties of the observed phonon branches can be extracted using a model for the quadratic dependence in terms of a Zeeman splitting and diamagnetic shift according to 2 , where h is the Planck constant, f TO is the TO phonon frequency at zero magnetic field, g* is the effective g-factor, μ B is the Bohr magneton, and σ dia is the diamagnetic shift coefficient (19). We used this equation in Fig.…”
Section: Giant Magnetic Moments Of Phonons In the Tci Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Chiral phonons, which are collective oscillations of a crystal lattice, exhibit a definitive handedness, setting them apart from traditional textbook examples that correspond to achiral modes. Although the non-zero total pseudoangular momentum (PAM) is enabled by inversion symmetry breaking in two-dimensional materials, the chiral motion of sublattices is present, even preserving this symmetry. The burgeoning interest in this collective chiral motion of the atoms has positioned them at the epicenter of an incipient but expanding research frontier. Given the long history of remarkable effects arising due to electron–phonon interactions, a natural question is whether the chirality of phonons may impart remarkable effects on electrons via their interaction. Previous studies have suggested that the interaction with one zone boundary mode with chiral displacement of the atoms can induce co-propagating edge states and that chiral phonons may incite unconventional and high-temperature superconductivity …”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to argue that the different conclusions reached from these two experiments are due to the technique difference, as electron diffraction should induce more strain than X-ray diffraction. Instead, Tauchert et al [29] found an anisotropic diffraction pattern that follows the initial magnetization of their sample, which they attributed to the polarized phonon involvement, but phonons are rarely magnetically active [30] and the longlasting associated orbital moment of the electron observed in He atoms [31] cast doubts on this interpretation. The key to resolve these difficult issues is to find the force on the atoms.…”
Section: Introductionmentioning
confidence: 99%